Ultrasound-guided biopsy of the prostate: New updates - Onur, Mehmet Ruhi; Turgut, Ahmet Tuncay; Dogra, Vikram (W.B. Saunders, 2014)
The main indications for transrectal ultrasound (TRUS)-guided prostate biopsy are abnormal digital rectal examination or increased prostate-specific antigen level. TRUS-guided prostate biopsy involves sampling 12 cores from midparasagittal and lateral aspects of the base, midgland, and apex of the prostate. Saturation biopsy should be reserved for repeat biopsy in the setting of negative results on initial biopsy in patients who are still strongly suspected to have prostate cancer. Advanced imaging techniques can be used in targeted prostate biopsy to increase sensitivity of biopsy in the detection of cancer and decrease the number of biopsy cores. © 2014 Elsevier Inc.
Keywords: Biopsy; Prostate; Transrectal ultrasonography